Effect of dietary lysine on the growth performance of Pangasius hypophthalmus - Diana Rachmawati; Dewi Nurhayati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
The success of intensive striped catfish (Pangasius hypophthalmus) cultivation requires quality feed that contains not only protein according to fish needs but also a complete essential amino acid profile to support the fish growth. One solution to overcome this problem is done through the addition of lysine in the feed commercial. This study aimed to examine the effect of lysine addition on the efficiency of feed utilization, growth and body composition of striped catfish (P. hypophthalmus). The study consisted of 4 (four) treatments those were with dosages of 0% / kg of feed (A); 0.6% / kg of feed (B); 1.2% / kg of feed (C); and 2.4% / kg of feed (D) of lysine for every kg of feed. The experimental diet in this study was a commercial feed in the form of pellets which was added with the lysine. A fixed feeding rate of 5%/weight of biomass/day was applied at frequency 3 times a day. The experimental fish used were striped catfish fingerling has an average weight of 4.13 ± 0.26 g/individuals. The results showed that the addition 1,2% / kg of lysine to the diet increased SGR, EFU, FCR, PER and protein content of the body composition of striped catfish.